Improving Female Basketball Shooting Accuracy Using Corrective and Stability Exercises (British Journal of Multidisciplinary and Advanced Studies, 2024)
Developing effective training methods to enhance shooting accuracy in women’s basketball provides key insights into precision fundamentals, thus elevating the gameplay quality and competitiveness. This study evaluated the effectiveness of targeted corrective and stability exercises in enhancing shooting accuracy among female basketball players. The quasi-experimental study involved 70 female students, from a public middle school in Villanueva North District, Misamis Oriental, Philippines. They were divided into two groups: Corrective Exercises and Stability Exercises groups. The participants’ pretest and posttest scores were analyzed using descriptive statistics and T-tests. The results indicated that before the intervention, participants in both groups demonstrated poor shooting accuracy with slight improvement following the intervention. The comparable levels of improvement between the two groups suggest that each type of exercise is equally effective in improving basketball shooting accuracy. Results suggest that an exercise program grounded in the Principle of Motor Learning, which breaks down complex actions for more effective practice, can enhance basketball shooting accuracy despite physical asymmetries and balance issues. The study recommends that educators and coaches implement structured physical activities to boost students’ shooting accuracy. It also urges future research to explore comprehensive training programs and demographics of shooting accuracy using corrective and stability exercises.